Heroes at the gates appeal and value in the Homeric epics from the archaic through the classical period - Fox, Peta Ann (Rhodes University, Faculty of Humanities, School of Languages, 2011)
This thesis raises and explores questions concerning the popularity of the Homeric poems in ancient Greece. It asks why the Iliad and Odyssey held such continuing appeal among the Greeks of the Archaic and Classical age. Cultural products such as poetry cannot be separated from the sociopolitical conditions in which and for which they were originally composed and received. Working on the basis that the extent of Homer's appeal was inspired and sustained by the peculiar and determining historical circumstances, I set out to explore the relation of the social, political and ethical conditions and values of Archaic and Classical Greece to those portrayed in the Homeric poems. The Greeks, at the time during which Homer was composing his poems, had begun to establish a new form of social organisation: the polis. By examining historical, literary and philosophical texts from the Archaic and Classical age, I explore the manner in which Greek society attempted to reorganise and reconstitute itself in a different way, developing original modes of social and political activity which the new needs and goals of their new social reality demanded. I then turn to examine Homer's treatment of and response to this social context, and explore the various ways in which Homer was able to reinterpret and reinvent the inherited stories of adventure and warfare in order to compose poetry that not only looks back to the highly centralised and bureaucratic society of the Mycenaean world, but also looks forward, insistently so, to the urban reality of the present. I argue that Homer's conflation of a remembered mythical age with the contemporary conditions and values of Archaic and Classical Greece aroused in his audiences a new perception and understanding of human existence in the altered sociopolitical conditions of the polis and, in so doing, ultimately contributed to the development of new ideas on the manner in which the Greeks could best live together in their new social world.
Keywords: Homer -- Iliad; Homer -- Odyssey; Homer -- Criticism and interpretation; Homer -- Influence; Epic poetry, Greek -- History and criticism